2018
DOI: 10.1155/2018/3120185
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Portal Vein Thrombosis in HCC Patients

Abstract: Macroscopic portal vein invasion (PVT) by hepatocellular carcinoma (HCC) in the liver is one of the most important negative prognostic factors for HCC patients. The characteristics of a large cohort of such patients were examined. We found that the percent of patients with PVT significantly increased with increasing maximum tumor diameter (MTD), from 13.7% with tumors of MTD <5cm to 56.4% with tumors of MTD >10cm. There were similar numbers of HCC patients with very large tumors with and without PVT. Thus, MTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…Some randomized controlled studies have been indicated that adjuvant PA-TACE treatment could archive clinical benefits for patients suffering from HCC larger than 5 cm (<5 cm) in diameter, macroscopic vascular invasion or multiple nodules 3032. Similar results were observed in clinical studies focused on prognosis analysis of patients with m-PVTT (macroscopic portal vein tumor thrombus) after surgical operation 3335…”
Section: Discussionsupporting
confidence: 63%
“…Some randomized controlled studies have been indicated that adjuvant PA-TACE treatment could archive clinical benefits for patients suffering from HCC larger than 5 cm (<5 cm) in diameter, macroscopic vascular invasion or multiple nodules 3032. Similar results were observed in clinical studies focused on prognosis analysis of patients with m-PVTT (macroscopic portal vein tumor thrombus) after surgical operation 3335…”
Section: Discussionsupporting
confidence: 63%
“…HCC aggressiveness factors of PVT, AFP, or multifocality have been previously shown to correlate with the increase in tumor size or MTD. [22][23][24][25][26][27] Whether this is causal or mere association has not been clarified. The two most likely hypotheses to explain the relation of size to other aggressiveness factors are the probability of aggressiveness factors per increased unit of tumor size versus an increased tumor size producing more factors that stimulate tumor invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Or does 5 cm mark a watershed in HCC biology, with > 5 cm tumors exhibiting more aggressive features? A partial answer is that there is an increase in portal vein invasion and in AFP levels with an increase in HCC size[ 18 ]. This may explain the high (70%) incidence of PVT positivity in these larger tumors, as shown in Table 1 and 2 .…”
Section: Discussionmentioning
confidence: 99%